THE USE OF DIETHANOLAMINE AS A CO2 ABSORBENT IN WAS TAKE THE DETERMINATION CORAL REEF AGE IN BARRANG LOMPO ISLAND SPERMONDE ISLANDS THROUGH MEASUREMENTS OF 14C ACTIVITY BY LIQUID SCINTILLATION COUNTING (LSC) METHOD - Jumiati Bunga Matande; Muhammad Zakir; Alfian Noor (Hasanuddin University, 2017)
Research on the use of diethanolamine (DEA) as a CO2 absorbent in was take the determination coral reef age in Barrang Lompo Island, Spermonde Islands through measurements of 14C activity by liquid scintillation Counting method (LSC) was carried our. Coral reef sample of the island Barrang Lompo at coordinates 5 ° 06 '49